Posisi Perempuan dalam Revolusi Prancis Abad 18 - Silva, Ray; Fitrisia, Azmi; Naldi, Hendra; Ompi, Ezra Olly (Jurnal Kronologi, 2024)
The 18th-century French Revolution stands as one of the most significant events in world history, ushering in sweeping changes in social, political, and economic structures. This article aims to explore and analyze the involvement of women in various revolutionary activities, as well as the changes in their rights and social positions during and after the revolution. The research methodology employed is historical research, encompassing heuristic approaches, source criticism to assess authenticity and data credibility, interpretation to understand the context and significance of events, and historiography. The findings reveal that women played crucial roles during the French Revolution in advocating for gender equality. The research elucidates that women were actively involved in various aspects of the revolution, including demonstrations, political organizations, and advocacy for their rights. Although many of their demands were not immediately realized post-revolution, their contributions planted seeds for future feminist movements and paved the way for broader social change.